(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The visionary of the linguistic heritage and the literary heritage that was left to us by the imams of the Association of Algerian Muslim Scholars clearly recognizes the lofty meanings and the noble aims that the Association’s flags sought to achieve and find to reach them. Perhaps the most prominent of these goals and the highest attention to these goals are seeking to promote the thought of Algerian society and the ideals of his ideas And to promote his ambitions in order to revive the spirit of authentic culture within it, and to embody the cultural aspect in its aspects, and consolidate the foundations of national identity in it. And the exploitation of this literary movement to achieve this purpose of awareness built by the members of the Association of scientists on the methodology of an integrated and a sequential process, starting from the report of the importance of Arabic language and the statement of virtue and great position with the clarification of its validity to describe the various arts and the study of other sciences, and also includes the search of the doors of Arabic and detail the issues at various levels, Download and use these mabahiths on the Qur’anic text and the Arab heritage of poetic and prose to clarify the meanings and meanings. This article seeks to analyze and analyze some of the linguistic contributions that have been made in this regard in the various works of the imams of the Association of Algerian Muslim Scholars through many works, lectures and articles, such as the linguistic contributions of its president, Abdelhamid Ben Badis, Us and other writers and flags of the Assembly. Keywords- Linguistics, Civilization, Association of savenets, Teaching.